Two new combinations in Erythranthe section Simiolus (Phrymaceae) for the flora of Chile - Watson, John Michael; Flores, Ana Rosa (Phytotaxa, 2014)
Two Chilean members of Mimulus, M. minimus and M. depressus var. ciminum, are transfered to Erythranthe as E. minima and E. depressa var. ciminum respectively.